IPSC derived progenitors - Birbrair, Alexander (Advances in stem cell biology ;, 2022)
IPSC Derived Progenitors, Volume Thirteen in the Advances in Stem Cell Biology series is a timely collection of information and new discoveries in the field of stem cell biology. The book addresses the importance of induced pluripotent stems cells and how can they be differentiated into different progenitors. Progenitors cells are often the first-step to making more differentiating cell types. This volume addresses iPSCs derived from bone, dental pulp, craniofacial, neural stem cells, otic, cardiac, and much more. The volume is written for researchers and scientists in stem cell therapy, cell biology, regenerative medicine, organ transplantation, and is contributed by world-renowned authors.